1977
DOI: 10.1097/00004032-197706000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Behavior of Cesium-137 in Cement-waste Composites

Abstract: To assess the safety for disposal of a radioactive waste-cement composite, the leaching of I3'Cs from a waste composite into a surrounding fluid has been studied. Leaching tests were carried out in accordance with a method recommended by IAEA. The leachability was measured as functions of waste to cement ratio (Wa/C), concentration of the salt (Na,SO,), temperature of leachant and curing time of specimens.The fraction of 137Cs leached from a specimen of Portland cement is 0.3-0.4 at the leaching time of 100 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…Leaching mechanism can be classified into two general categories: 1) initial wash off and 2) diffusion control. On the basis of parameters A 1 and leaching coefficient D e [8], in different cement matrix formulations, we have noticed that leaching rate of Cs 137 > Co 60 which is matched with other studies [1][2][3][4]. We have also observed that Cs 137 and Co 60 cumulative amount of leached, f, decreased in order f (C-II) > f (C-IV) > f (C-I) > f (C-III).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Leaching mechanism can be classified into two general categories: 1) initial wash off and 2) diffusion control. On the basis of parameters A 1 and leaching coefficient D e [8], in different cement matrix formulations, we have noticed that leaching rate of Cs 137 > Co 60 which is matched with other studies [1][2][3][4]. We have also observed that Cs 137 and Co 60 cumulative amount of leached, f, decreased in order f (C-II) > f (C-IV) > f (C-I) > f (C-III).…”
Section: Resultssupporting
confidence: 85%
“…The dispersion of radionuclides in porous materials, such as grout or concrete, is described using a one dimensional differential model [1][2][3].…”
Section: Radionuclide Migration Through Porous Materials and Modellinmentioning
confidence: 99%
See 1 more Smart Citation
“…Th ree methods are compared with respect to their applicability to experimental leaching data [6,10,13,14].…”
Section: Th Eoretical Methodsmentioning
confidence: 99%
“…A szivárgási vizsgálatot a Vinca Intézet által kifejlesztett eredeti módszerrel [1, 2, 3, 4, 5] végeztük. A radioaktív anyag egy cementes kompozit mátrixból való kiszivárgásának szállítási jelenségeit az elméleti egyenleteken [6,10] alapuló három módszer alkalmazásával vizsgáltuk. Ezek a következők voltak: egy sima forrásra vonatkozó diffúziós egyenlet, egy első fokú egyenlettel párosított diffúziós egyenlet, és egy polinom egyenletet használó empirikus módszer.…”
Section: Szállítási Jelenségek Matematikai Modellezése Porózus Beton unclassified